: indonesia - Meiliyanti, Siti Zahra; Aulia Mustika Ilmiani; Apri Wardana Ritonga (Prodi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam As-Sunnah, 2025)
In the era of modern learning, interactive dynamics have become an important aspect in creating an active and meaningful learning process. However, in Nahwu learning at universities, students often still show passive learning patterns with a dominance of one-way lecture methods. This condition hinders student engagement and conceptual understanding of Arabic grammar structure. This study aims to explain how the use of Guided Cooperative Learning (GCL) affects Nahwu lessons and how it makes classes more interactive. This study uses a qualitative descriptive method that focuses on one lecturer and 38 students in the fourth semester of the Arabic Language Education Program at UIN Palangka Raya. Information was collected by observing three in-depth class sessions, conducting detailed discussions, and reviewing lesson plans; then analyzed using the Miles and Huberman interactive model. The results of the study show that the use of GCL makes students more active in participating, interact more with each other, and understand i'rab better. The lecturer acts as the main guide in creating a classroom environment where everyone works together and thinks deeply.